2006
DOI: 10.1007/s10495-006-4002-0
|View full text |Cite
|
Sign up to set email alerts
|

Increasing ornithine decarboxylase activity is another way of prolactin preventing methotrexate-induced apoptosis: Crosstalk between ODC and BCL-2

Abstract: Prolactin has more than 300 separate functions including affecting mammary growth, differentiation, secretion and anti-apoptosis. In the previous studies, prolactin induced Bcl-2 expression to prevent apoptosis and also provoked the activity of ornithine decarboxylase (ODC). Our previous data showed that ODC overexpression upregulates Bcl-2 and prevents tumor necrosis factor alpha (TNF-alpha)- and methotrexate (MTX)-induced apoptosis. Here, we further investigate whether prolactin prevents MTX-induced apoptosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 52 publications
(66 reference statements)
1
19
0
Order By: Relevance
“…It was evidenced to reduce intracellular glutathione-based antioxidants and produce oxygen free radicals during its intracellular metabolism. This oxidant/antioxidant imbalance leads to lipid peroxidation followed by organelles and plasma membranes lysis [39,40] . Such lipid peroxidation was enforced by significantly increased MDA value, acinar and ductal cell membrane rupture and ductal epithelial discontinuity in MTX group.…”
Section: Discussionmentioning
confidence: 99%
“…It was evidenced to reduce intracellular glutathione-based antioxidants and produce oxygen free radicals during its intracellular metabolism. This oxidant/antioxidant imbalance leads to lipid peroxidation followed by organelles and plasma membranes lysis [39,40] . Such lipid peroxidation was enforced by significantly increased MDA value, acinar and ductal cell membrane rupture and ductal epithelial discontinuity in MTX group.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous studies, overexpression of ODC represses the extrinsic death pathway of TNFα-induced apoptosis [4] and blocks the intrinsic pathway of chemotherapeutic drug-induced apoptosis [5]. In addition, overexpressed ODC up-regulates the expression of Bcl-2 to enhance the anti-apoptotic effect of ODC [6]. Therefore, we are interested in the molecular and cellular function of the natural ODC inhibitor, antizyme, in the apoptosis of haematopoietic cells.…”
Section: Discussionmentioning
confidence: 99%
“…The supernatant was boiled in loading buffer and an aliquot corresponding to 100 µg of protein was separated by SDS-PAGE. After blotting, the membranes were incubated with anti-antizyme (MDBio, TWN), anti-ODC, anti-p53, anti-p21, anti-Bax, anti-Bcl-2, anti-Bcl-xL, anti-cyclin E, anti-cyclin D, anti-cyclin A, anticyclin B, anti-cyclin-dependent kinase 1 (Cdk1), anti-Cdk2, anti-Cdk4, anti-cytochrome c, anti-caspase 9, anti-caspase 3, anti-Apaf-1, anti-PARP and anti-actin antibodies (Lab Vision and Santa Cruz, CA) for 6 h and the second antibody labeled with horseradish-peroxidase was adjacently incubated Enzyme activity assay of ODC ODC enzyme activity was assayed at 37 • C by measuring its product, putrescine, as described previously [6]. Samples were suspended in ODC buffer ( …”
Section: Immunoblottingmentioning
confidence: 99%
See 1 more Smart Citation
“…Another group reported that pretreatment of ovarian carcinoma cells with PRL inhibits cisplatin-induced cell death (Asai-Sato et al 2005). PRL also antagonizes apoptosis caused by methotrexate, an antifolate agent, in human promyelocytic leukemia HL-60 cells (Hsu et al 2006).…”
Section: Prl and Chemoresistancementioning
confidence: 99%